Accelerating of Pink Pigment Excretion from Cyanobacterium Oscillatoria by Co-Cultivation with Anabaena - DWI SUSILANINGSIH (Bogor Agricultural University, Indonesia, 2007)
The freshwater cyanobacterium Oscillatoria BTCC/A 0004 excretes pink pigment containing lipoproteins with molecular weights of about 10 kDa. This pigment has surfactant properties with strong emulsification activity toward several hydrocarbons. This extracellular metabolite was suspected as toxin or allelochemical in their habitat. In this study, I investigated the effect of co-cultivation of Oscillatoria with Anabaena variabilis on the pigment excretion to explore the physiological roles of this pigment in its natural environment. The dead or viable cells and medium of A. variabilis were added into Oscillatoria cultures. Results showed that co-cultivation of free viable cells of A. variabilis enhanced the excretion of pigment without effect on the cell growth. Co-cultivation with viable cells in separated method and dead cells did not influenced the pigment production. The addition of A. variabilis medium was slightly increased the excretion of the pigment. Those results indicated that direct contact with A. variabilis caused Oscillatoria released a certain signaling compound. Key words: Oscillatoria, Anabaena variabilis, biosurfactant, cyanobacterium, pink pigment